Quantum phase transitions out of a Z(2) x Z(2) topological phase - Jahromi, Saeed S.; Masoudi, S. Farhad; Kargarian, Mehdi; Schmidt, Kai Phillip (Physical Review B, 2013)
We investigate the low-energy spectral properties and robustness of the topological phase of color code, which is a quantum spin model for the aim of fault-tolerant quantum computation, in the presence of a uniform magnetic field or Ising interactions, using high-order series expansion and exact diagonalization. In a uniform magnetic field, we find first-order phase transitions in all field directions. In contrast, our results for the Ising interactions unveil that for strong enough Ising couplings, the Z(2) x Z(2) topological phase of color code breaks down to symmetry broken phases by first-or second-order phase transitions.